(untitled) (Hydro Nepal: Journal of Water, Energy and Environment, 2009)
As food need rises, Nepal’s reliance on irrigated agriculture does increase. Increased production to satisfy the food demand of the future must essentially come from intensification, not from expansion of agriculture. Intensification potential of irrigated agriculture is much higher than rainfed system. Technologies, professionals and farmers should go together to achieve greater impacts and ensure the country’s food security. Key words: Irrigated agriculture, food security, farmer participation, conjunctive use, physical infrastructure, integrated water resource management, Nepal doi: 10.3126/hn.v3i0.1918 Hydro Nepal Journal of Water, Energy and Environment Issue No. 3, July 2008. Page 35-37